Autism Associated with B-Vitamin Deficiency Linked to Sugar Intake and Alcohol Consumption - Shamberger, Raymond J. (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
Objectives: Autism rates in the United States are increasing at a rate of 10-15% per year. This study uses nutritional epidemiology and relates autism rates to the total B-vitamin intakes. The total amounts of B-vitamins are then compared to the previously established minimal daily requirements to see if the intakes are adequate. The apparent lower B-vitamins may result from the increased consumption of sugar and alcohol which are devoid of vitamins, minerals, protein, fat and antioxidants. Study Design: The autism rate was then compared to the percent exclusive per cent breast feeding from 2000-2004 as well as 2007-2010. Other comparisons were made between the statewide exclusive breast feeding and the binge drinking per state. The percentage of infants who participated in Washington state WIC (Womens Infant & Childrens) program were also compared to the autism rate in each county. The autism rate among 8 year olds when compared to the % increase of sugar consumption from 2002 to 2010 also showed an increase in the autism rate. Results: The total amounts of B vitamins in breast milk seemed to be inadequate compared to published mdrs. There was also a direct relationship to the autism rate with the women who were breast feeding from 2000-2004 and 2007-2010. Increased autism rates were related to increased sugar consumption and to an increased alcohol intake. Conclusions: The mothers who are exclusively breast feeding should continue their prenatal vitamins. Sugar intake and alcohol consumption should be decreased. The results suggest that autism is nutritionally related.